'Everybody learns English, and so do I': The dominance of English and its effects on individuals: What English learning means to college students in Taiwan?. Issue 1 (11th December 2015) - Huang, I-Chen
Abstract : In some Asia-Pacific countries, English is neither an ethnic heritage nor a colonial legacy. The dominant position of English can also be a result of it being the common language for worldwide communication. The superiority of the English language in such countries manifests itself in language policy and national curricula which leads to a frantic pursuit of English. An educational trend in China, Japan, Taiwan, and Vietnam is to start English instruction early to give children an edge in second language acquisition. A rationale used for this is the positive relationship between a nation's international competiveness and the English language competence of its citizens (Baldauf & Nguyen, 2013; Hu, 2009; Park, 2009). One example of a nationwide English learning movement is 'the-earlier-the-better' in Taiwan. To win elections, electoral candidates used to propose English instruction to be available at Grade 1 (age of 6) although the Ministry of Education ruled for Grade 5 (age of 10) to be the year for English to be introduced (Chang, 2009). Another example of early English learning is overseas study in South Korea. Young children are sent to North America to receive long-term education so that they can learn to speak English without a Korean accent (Song, 2010).